Cerebrovascular ultrasound: theory, practice, and future developments - Hennerici, Michael G.; Meairs, Stephen (Cambridge University Press, 2001)
Ultrasound provides a unique diagnostic perspective in cerebrovascular disorders, with extremely high temporal resolution and excellent spatial display of extracranial arteries, brain structures and cerebral vessels. This comprehensive text covers the fundamentals of ultrasound physics, new technology, and clinical applications in all ages. It provides a firm grounding in hemodynamics and describes computational models for study of the cerebral circulation. Extracranial applications in assessing the carotid and vertebral arteries are discussed in detail, as are intracranial Doppler applications in stroke, subarachnoid hemorrhage, arteriovenous malformations, interventional and surgical procedures, and the detection and monitoring of cerebral microembolism. These and other topics, both clinical and technical, are presented by leading authorities in the field, with extensive illustrations, and tables are included for the standardized classification of cerebrovascular diseases based on international consensus conferences. For clinicians and clinical neuroscientists this is the definitive reference text in cerebrovascular ultrasound
Online publication date: July 2014
Title from publisher's bibliographic system (viewed on 05 Oct 2015), gesehen am 10.03.2021
Keywords: Aufsatzsammlung; Ultraschalldiagnostik; Hirngefäßkrankheit